The upwind hybrid difference methods for a convection diffusion equation - Jeon, Youngmok; Tran, Mai Lan (Applied Numerical Mathematics, 2018)
We propose the upwind hybrid difference method and its penalized version for the convection dominated diffusion equation. The hybrid difference method is composed of two types of approximations: one is the finite difference approximation of PDEs within cells (cell FD) and the other is the interface finite difference (interface FD) on edges of cells. The interface finite difference is derived from continuity of normal fluxes. The penalty method is obtained by adding small diffusion in the interface FD. The penalty term makes it possible to reduce severe numerical oscillations in the upwind hybrid difference solutions. The penalty parameter is designed to be some power of the grid size. A complete stability is provided. Convergence estimates seems to be conservative according to our numerical experiments. To exposit convergence property and controllability of numerical oscillations several numerical tests are provided.
Keywords: Convection-diffusion equations; Convection-dominated diffusion; Convergence properties; Difference method; Finite difference approximations; Numerical experiments; Penalty methods; Upwind method; Convection diffusion equations; Hybrid difference method; Penalty method; Upwind method